The conundrum of care in the construction of professional identity - Bin Wu; Nesta Devine (New Zealand Journal of Teachers' Work)
The notion of 'professional' is built on a concept of traditionally male professions and patriarchal social orders. ECEC (early childhood education and care), however, is a female-dominated field characterised by its unique caring practice that is more salient when working with infants and toddlers. This study investigates how a group of Australian early childhood preservice teachers presented themselves professionally on Instagram, in relation to respective infant (0-2) and kindergarten (3-5) practica. Data were drawn from focus group discussions about how the participants shared their practicum experiences on social media, Instagram. The paper is guided by Foucault’s concepts of technologies of the self and self writing. The findings reveal two thematic narratives: 1) in the context of the kindergarten placement, the posts constitute a journey of continuous improvement against all odds. 2) In contrast, the infant placement experiences evoke a sense of struggle and renunciation. The paper concludes with implications for further study beyond the Australian context.